2019
DOI: 10.24033/bsmf.2778
|View full text |Cite
|
Sign up to set email alerts
|

The Riemann-Hilbert mapping for $\mathfrak{sl}_2$ systems over genus two curves

Abstract: We prove in two different ways that the monodromy map from the space of irreducible sl 2 -differential-systems on genus two Riemann surfaces, towards the character variety of SL 2 -representations of the fundamental group, is a local diffeomorphism. We also show that this is no longer true in the higher genus case. Our work is motivated by a question raised byÉtienne Ghys about Margulis' problem: the existence of curves of negative Euler characteristic in compact quotients of SL 2 (C). Nous montrons de deux ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…M [11], [4], [5] (any holomorphic connection on a Riemann surface is automatically integrable). Since the fundamental group of a compact complex torus T is abelian, there is no irreducible integrable connection on a rank two bundle over T. Also, the pullback of a reducible connection is reducible.…”
Section: Properties Of the Pro-algebraic Group Scheme θmentioning
confidence: 99%
See 1 more Smart Citation
“…M [11], [4], [5] (any holomorphic connection on a Riemann surface is automatically integrable). Since the fundamental group of a compact complex torus T is abelian, there is no irreducible integrable connection on a rank two bundle over T. Also, the pullback of a reducible connection is reducible.…”
Section: Properties Of the Pro-algebraic Group Scheme θmentioning
confidence: 99%
“…While they can't contain a complex surface [19, p. 239, Theorem 2], it is not known whether they can 2 I. Biswas, J. P. dos Santos, S. Dumitrescu and S. Heller contain compact Riemann surfaces of genus g > 1. A positive answer to Ghys' question would provide a nontrivial holomorphic map from the Riemann surface M to the quotient of SL(2, C) by the cocompact lattice containing the image of the monodromy homomorphism for D. In fact the two problems are equivalent (see [11] for explanations for the origin of Ghys' question).…”
Section: Introductionmentioning
confidence: 99%
“…Differentials with zero reduced exponents at all punctures correspond to parabolic projective structures (see [Kra69; Kra71b; Kra71a; DD17; HD19]). Differentials with integer non-zero reduced exponents and trivial holonomy at the punctures (apparent singularities) correspond to branched projective structures (see [Man72;CDF14a;Cal+19;FR21]). The next lemma implies that for structures in P (Σ) the absolute value of the exponent at a puncture coincides with the value of the index, as defined in §3.4.…”
Section: The Complex Analytic Point Of Viewmentioning
confidence: 99%
“…A natural question is to better understand the complex geometry of these deformation spaces, which is of course best studied in terms of this projection. This is moreover motivated by the aforementioned correspondence proved in [CDHL19] between sl 2 -systems with irreducible monodromy ρ on a Riemann surface of genus g ≥ 2 and rational curves in M 2g−2,ρ ; more precisely they showed that if π : M 2g−2,ρ → T (S) has a fiber with at least three points, then that fiber is actually a rational curve and ρ is the monodromy of some sl 2 -system.…”
Section: Introductionmentioning
confidence: 98%
“…Our main motivation for this work lies in a more recent paper by Calsamiglia-Deroin-Heu-Loray (see [CDHL19]) in which they study sl 2 -systems on a closed surface of genus g ≥ 2, i.e. systems of first order ODEs of the form…”
Section: Introductionmentioning
confidence: 99%